Sirtuin 4 contributes to heart failure development by increasing mitochondrial oxidative stress. (25th November 2020) - Koentges, C; Khan, E; Birkle, S; Hoelscher, M; Pfeil, K; Gollmer, J; Hoffmann, M.M; Bode, C; Zirlik, A; Bugger, H
Abstract: : Sirtuin 4 (SIRT4) is a mitochondrial NAD+-dependent deacylase which inhibits the oxidation of glucose and fatty acids, and has been implicated in the regulation of oxidative stress. Given the importance of cardiac energy depletion and ROS during heart failure development, we aimed to define the role of SIRT4 in the development of heart failure. Mice with deletion (SIRT4−/−) or overexpression (SIRT4 TG) of SIRT4 were subjected to transverse aortic constriction (TAC) for 12 weeks or underwent sham procedures. Using echocardiography, ejection fraction (EF) was not different between SIRT4 TG and WT mice subjected to sham operations. In contrast, TAC induced a more pronounced decrease in EF (35% vs. 51%; p<0.05), and a more pronounced increase in LV endsystolic diameter (4.5mm vs. 3.6mm; p<0.05) and myocardial fibrosis (2.2-fold; p<0.05) in SIRT4 TG mice compared to WT mice. Myocardial levels of the lipid peroxidation product 4-hydroxynonenal were increased in WT mice following TAC and were synergistically increased in SIRT4 TG mice following TAC (+66% vs. WT TAC; p<0.05). Administration of the mitochondria-targeted antioxidant MitoQ normalized 4-hydroxynonenal levels, markedly attenuated the decline in EF and almost normalized endsystolic LV diameter in SIRT4 TG mice following TAC. Cardiac function and morphology were unaffected in SIRT4−/− mice during normal or increased workload conditions. Thus, while SIRT4 is not required to maintain cardiac function even in response to increased energy demands, increased expression of SIRT4 accelerates the development of heart failure following TAC, at least in part due to increased mitochondrial oxidative stress. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): German Research Foundation